MTL genotypes, phenotypic switching, and susceptibility profiles of Candida parapsilosis species group compared to Lodderomyces elongisporus. - Aylin Döğen; Banu Metin; Macit Ilkit; G Sybren de Hoog; Joseph Heitman (PLoS ONE)
Reference isolates of Candida parapsilosis (n = 8), Candida metapsilosis (n = 6), Candida orthopsilosis (n = 7), and Lodderomyces elongisporus (n = 11) were analyzed to gain insight into their pathobiology and virulence mechanisms. Initial evaluation using BBL Chromagar Candida medium misidentified L. elongisporus isolates as C. albicans. Polymerase chain reaction analysis of isolate MTL idiomorphs revealed that all C. parapsilosis isolates were MTLa homozygous and no MTL α1, α2, a1, or a2 gene was detected in L. elongisporus isolates. For C. orthopsilosis, two isolates were MTLa homozygous and five were MTL-heterozygous. Similarly, one C. metapsilosis isolate was MTLα homozygous whereas five were MTL-heterozygous. Isolate phenotypic switching analysis revealed potential phenotypic switching in the MTLα homozygous C. metapsilosis isolate, resulting in concomitant elongated cell formation. Minimum inhibitory concentrations of fluconazole (FLC) and FK506, alone or in combination, were determined by checkerboard assay, with data analyzed using the fractional inhibitory concentration index model. Synergistic or additive effects of these compounds were commonly observed in C. parapsilosis and L. elongisporus isolates. No killer activity was observed in the studied isolates, as determined phenotypically. No significant difference in virulence was seen for the four species in a Galleria mellonella model (P > 0.05). In conclusion, our results demonstrated phenotypic switching of C. metapsilosis CBS 2315 and that FLC and FK506 represent a promising drug combination against C. parapsilosis and L. elongisporus. The findings of the present study contribute to our understanding of the biology, diagnosis, and new possible treatments of the C. parapsilosis species group and L. elongisporus.